2015
DOI: 10.1039/c5ra00187k
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid Sr-doped TiO2/magnetic Ni0.6Zn0.4Fe2O4 for enhanced separation and photodegradation of organics under visible light

Abstract: Titanium dioxide (TiO2) has been intensively used as a photocatalyst for the degradation of organic pollutants in water, but is typically obstacle by a low efficiency, costly separation, limited visible light response, and poor recyclability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…24,25 The introduction of Zn 2+ into NiFe 2 O 4 enhanced the catalytic and magnetic properties of the resulting nanocatalysts. 26 The reported dark/ambient nanocatalysts degraded various environmental contaminants by Fenton-like reactions, and a synergetic effect was achieved when FeO 3 or CuO was attached to other metal oxides. 22,23 Considering the available reported literature in the eld of ambient catalytic efficiency for various nanocatalysts, in the present work, CoFe 2 O 4 /ZnO hybrid nanocomposites were synthesized using an economically viable low-frequency ultrasoundassisted method to enhance the catalytic and magnetic properties of the resulting nanocatalysts.…”
Section: Introductionmentioning
confidence: 95%
“…24,25 The introduction of Zn 2+ into NiFe 2 O 4 enhanced the catalytic and magnetic properties of the resulting nanocatalysts. 26 The reported dark/ambient nanocatalysts degraded various environmental contaminants by Fenton-like reactions, and a synergetic effect was achieved when FeO 3 or CuO was attached to other metal oxides. 22,23 Considering the available reported literature in the eld of ambient catalytic efficiency for various nanocatalysts, in the present work, CoFe 2 O 4 /ZnO hybrid nanocomposites were synthesized using an economically viable low-frequency ultrasoundassisted method to enhance the catalytic and magnetic properties of the resulting nanocatalysts.…”
Section: Introductionmentioning
confidence: 95%
“…Figure 3 shows the high-resolution Ti 2p, O 1s, N 1s, and Ni 2p XPS spectra of the N-TiO 2 /1.0 wt% Ni(OH) 2 . As is shown for Ti 2p, peaks at 458.5 and 464.3 eV could be ascribed to Ti 2p 3/2 and Ti 2p 1/2 of TiO 2 , respectively, indicating the existence of Ti 4+ in the sample [24][25][26]; while for O 1s, signals of lattice oxygen (titanium-oxygen-titanium, 529.7 eV) and hydroxyl oxygen (Ti-OH and Ni-OH, 531.4 eV) are observed [27] (Figure 3b). A weak characteristic peak (N1s) at 399.9 eV attributes to the signal combination of weakly charged nitrogen species with C, H, or O atoms [28] (Figure 3c), and demonstrates the successful diffusion of nitrogen into the TiO 2 lattice at interstitial positions [29,30].…”
Section: Resultsmentioning
confidence: 92%
“…Here we have hypothesised that (1) the doping of Ni0.5Zn0.5Fe2O4 nanocrystals as sensitive to magnetic field could facilitates catalyst separation from the aqueous dispersion as well as may promote visible light absorbtion (2) enhance light harvesting and photocorrosion inhibition due to enhanced conductivity of hybrid PANI [38] and (3) an interface formation between Ni0.5Zn0.5Fe2O4@Polyaniline and BiOCl and transit interfacial reaction process [39,40]. In our preliminary work it was found that the incorporation of as prepared polyaniline composite with low dose …”
Section: Introductionmentioning
confidence: 99%